Peran strategis public relations dalam meningkatkan reputasi perbankan syariah di era digital - Ramadhan, Azhar Zahira (Maliki Interdisciplinary Journal, 2024)
The rapid development of digital technology has transformed communication and interaction in the Islamic banking sector. In the tight competition with conventional banks and fintech, reputation is a critical factor for attracting and retaining customers. Public Relations (PR) plays a central role in building and maintaining the reputation of Islamic banks through effective communication, transparency, and education. However, PR faces challenges such as low financial literacy regarding Islamic finance, data security, and competition with more innovative conventional banks. This study aims to analyze the role of PR in enhancing the reputation of Islamic banking in the digital era and identify strategies that can be adopted to address these challenges. A descriptive qualitative method using literature review was employed. The findings are expected to contribute to reputation management in the Islamic banking sector.